(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda Panchakarmas are an all-time big name for both Ayurveda doctors and patients. Their efficacy of targeting the body holistically and evacuating toxins, thereby, addressing most of the problems of an individual makes it a hit. This paper aims at estimating the contribution of Purva Karma (procedures prior to instillation of medicine) in the outcome, especially in the context of Sneha Nasya (instillation of unctuous medicine). Nasal route of administration may help address the hitches accompanying to poor bioavailability, slow absorption, drug degradation, and possible adverse events in the gastro intestinal tract and avoids the first-pass metabolism in the liver. However, when considering nasal delivery, appropriate measures need to be taken to address the limitations of drug delivery in this region. Purva Karma starts with drug preparation and ends with stage of instillation of medicine (8 check points). The role of each of them on overcoming the limitations and delivering the results is reviewed.